National Prehospital Evidence-Based Guidelines Strategy: A Summary for EMS Stakeholders. (3rd March 2016) - Martin-Gill, Christian; Gaither, Joshua B.; Bigham, Blair L.; Myers, J. Brent; Kupas, Douglas F.; Spaite, Daniel W.
Abstract: Multiple national organizations have recommended and supported a national investment to increase the scientific evidence available to guide patient care delivered by Emergency Medical Services (EMS) and incorporate that evidence directly into EMS systems. Ongoing efforts seek to develop, implement, and evaluate prehospital evidence-based guidelines (EBGs) using the National Model Process created by a multidisciplinary panel of experts convened by the Federal Interagency Committee on EMS (FICEMS) and the National EMS Advisory Council (NEMSAC). Yet, these and other EBG efforts have occurred in relative isolation, with limited direct collaboration between national projects, and have experienced challenges in implementation of individual guidelines. There is a need to develop sustainable relationships among stakeholders that facilitate a common vision that facilitates EBG efforts. Herein, we summarize a National Strategy on EBGs developed by the National Association of EMS Physicians (NAEMSP) with involvement of 57 stakeholder organizations, and with the financial support of the National Highway Traffic Safety Administration (NHTSA) and the EMS for Children program. The Strategy proposes seven action items that support collaborative efforts in advancing prehospital EBGs. The first proposed action is creation of a Prehospital Guidelines Consortium (PGC) representing national medical and EMS organizations that have an interest in prehospital EBGs and their benefits to patient outcomes. Other action items include promoting research that supports creation and evaluates the impact of EBGs, promoting the development of new EBGs through improved stakeholder collaboration, and improving education on evidence-based medicine for all prehospital providers. The Strategy intends to facilitate implementation of EBGs by improving guideline dissemination and incorporation into protocols, and seeks to establish standardized evaluation methods for prehospital EBGs. Finally, the Strategy proposes that key stakeholder organizations financially support the Prehospital Guidelines Consortium as a means of implementing the Strategy, while together promoting additional funding for continued EBG efforts.